Diborylmethyl Group as a Transformable Building Block for the Diversification of Nitrogen‐Containing Molecules. (1st August 2022) - Hwang, Chiwon; Lee, Yeosan; Kim, Minjae; Seo, Younggyu; Cho, Seung Hwan
Abstract: The development of new approaches to installing diverse carbon fragments to a nitrogen atom has attracted considerable attention in chemical science. While numerous strategies have been devised to forge C(sp 3 )−N bonds, one conceptually powerful and straightforward approach is to insert a transformable sp 3 ‐carbon unit onto a nitrogen atom for modular diversification. Here we describe the successful synthesis of halo‐diborylmethanes and their applications to the preparation of nitrogen‐substituted diborylmethanes through their homologative coupling with a variety of nitrogen nucleophiles including biologically relevant molecules. This process exhibits a remarkably broad substrate scope, and the usefulness of the obtained compounds is demonstrated by the modular diversification of the diborylmethyl group to access various nitrogen‐containing molecules. Abstract : We established an efficient protocol for the preparation of halo‐diborylmethanes and their use in homologative coupling with nitrogen nucleophiles to generate various nitrogen‐substituted diborylmethanes. The diborylmethyl group installed onto the nitrogen atom served as a versatile synthetic handle, allowing for the programmed diversification of nitrogen‐containing molecules.